Terapi Rendam Kaki Menggunakan Air Hangat pada Lansia dalam Menurunkan Tekanan Darah - Ajeng Nurmaulina; Hendri Hadiyanto (Fakultas Kesehatan Universitas Muhammadiyah Sukabumi, 2021)
High blood pressure generally occurs without symptoms, most people do not feel anything even though their blood pressure is far above normal, so high blood pressure is also known as silent killer. High blood pressure can be controlled by pharmacological and non-pharmacological therapy. One of the managements of high blood pressure with non-pharmacological therapy is soaking the feet using warm water. This study aims to determine the effectiveness of soaking the feet using warm water in the elderly to decrease blood pressure. This research method uses descriptive qualitative research with a case study strategy. This research using one participation. This research was conducted by soaking foot using warm water with a temperature of 38 C once a day for three consecutive days for 25 minutes. The results obtained after doing therapy there is a decrease in blood pressure from 150/100 mmHg to 130/90 mmHg. It can be concluded that there is a significant effect of giving foot soak therapy using warm water to decrease blood pressure. This study suggests that foot soak therapy using warm water can be used as a non-pharmacological therapy for the elderly with high blood pressure